2012
DOI: 10.1063/1.3697702
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-dot nano-cavity lasers with Purcell-enhanced stimulated emission

Abstract: We present a rate equation model for quantum-dot light-emitting devices that take into account Purcell enhancement of both spontaneous emission and stimulated emission as well as the spectral profile of the optical and electronic density-of-states. We find that below threshold the β-factor in a quantum-dot nanolaser depends strongly on the pump. For quantum dots with linewidth comparable to that of the cavity, we then show that an otherwise non-lasing device can lase due to Purcell enhancement of the stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…The definition (16) for the background emission is necessary for subsequent comparison with our microscopic model which requires a fixed β, i.e., independent of the carrier number. In Appendix A we present the general procedure for computing the β factor.…”
Section: B Rate Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition (16) for the background emission is necessary for subsequent comparison with our microscopic model which requires a fixed β, i.e., independent of the carrier number. In Appendix A we present the general procedure for computing the β factor.…”
Section: B Rate Equationsmentioning
confidence: 99%
“…The intention of this paper is to clarify this situation by bridging the gap between a purely microscopic approach and a rate equation model that is suited for implementation in large-scale device simulations. We thus present the detailed derivation of our recently published rate equation model, 16 which naturally extends our previous models valid in the LED regime of spontaneous emission, 14,16 to account for spontaneous and stimulated emission rates in a self-consistent way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two important figures of merit of a nanolaser are its b-factor (the fraction of spontaneous emission that couples to the lasing mode) and the cavity mode volume (the spatial extension of the lasing mode). These can be determined by modelling the laser input-output curves with microcavity semiconductor laser rate equations 22 (cf. Fig.…”
mentioning
confidence: 99%
“…8,33 Neglecting the Purcell enhancement of stimulated emission would overlook the finite linewidth of the lasing modes, and result into a solution contradictory to the Einstein relation 34 and the prediction of microscopic model. 35 Therefore, it was suggested that a comprehensive rate equation analysis 36,37 including the aforementioned experimental evidences should be used. In this work, by means of a full rate equation model including the complete cavity QED effects, we can accurately investigate the optical properties of our organic-silicon PC nanoslot cavity light source in a self-consistent fashion.…”
Section: Introductionmentioning
confidence: 99%